Analysis of the Quality and Competence of Civil Servants Affecting Services at the Banyumas Regency Education Office - Ribka Novianeli; Denok Kurniasih (Spirit Publik: Jurnal Administrasi Publik, 2025)
This study analyzes the quality and competence of the State Civil Apparatus (ASN) that influence public services in the Banyumas Regency Education Office, because the Education Office is at the forefront of public services in the field of education. The core problem is that there is still a lack of quality and competence among ASN in managing technical and managerial skills, which causes ineffective services such as school management and aid distribution. Based on empirical data from the National Civil Service Agency (BKN, 2022), which shows that 35% of ASN in the region have a mismatch in competencies, the author raises this issue as a topic of discussion in this scientific article. The research method used a qualitative approach (processed using the Miles & Huberman (1994) technique) through interviews with informans, observation, and document analysis. The study found that the poor quality and competence of civil servants have a major impact on public service delivery. Therefore, the research suggests reforming the merit system, implementing solutions that align with leadership directions, and creating more opportunities for civil servants to enhance their skills through continuous training. These steps will help ensure that organizational goals are met effectively and that the quality of public services continues to improve.